Immobilization of Oat Bran Polyphenols in Complex Coacervates of Whey Protein and Malthodextrin - Zyaitdinov Damir R.; Ewteew Alexandr V.; Bannikova Anna V. (Техника и технология пищевых производств)
Introduction. Bioactive compounds are a very popular topic of modern food science, especially when it concerns obtaining polyphenols from cereals. The antiradical, antioxidant, and anti-inflammatory properties of these ingredients allow them to inhibit and prevent coronary, artery, and cardiovascular diseases, as well as several types of cancer. Encapsulation is an effective technology that protects bioactive ingredients during processing and storage. In addition, it also prevents any possible interaction with other food constituents. The research objective was to obtain effective tools of controlled delivery of bioactive compounds. The study featured whey protein as a wall material in combination with maltodextrin to encapsulate the bioactives from oat bran. Study objects and methods. The processed material was oat bran. The technology of its biotransformation was based on ultrasound processing and enzymatic hydrolysis. The antioxidant properties were determined using a coulometer of Expert – 006-antioxidants type (Econix-Expert LLC, Moscow, Russia). Separation and quantitative determination of extract were followed using a Stayer HPLC device (Akvilon, Russia) and a system column Phenomenex Luna 5u C18(2) (250×4.6 mm). The total phenolic content was measured by a modified Folin-Ciocalteu method. To prepare microcapsules, whey protein concentrate (WPC) and maltodextrin (MD) solutions were mixed at ratios 6:4, 4:6, and 5:5. After that, the mixes were treated by ultrasonication and 10% w/w of guar gum solution as double wall material. The encapsulation efficiency (EE) was determined as a ratio of encapsulated phenolic content to total phenolic content. A digestion protocol that simulates conditions of the human gastric and intestinal tract was adapted to investigate the release kinetics of the extracts. Results and discussion. Ferulic acid is the main antioxidant in cereals. Its amount during extraction was consistent with published data: 9.2 mg/mL after ultrasound exposure, 9.0 mg/mL after enzymatic extraction, and 8.6 mg/mL after chemical treatment. The antioxidant activity of the obtained polyphenols was quite high and reached 921 cu/mL. It depended on the concentration of the preparation in the solution and the extraction method. The polyphenols obtained by ultrasonic exposure and enzyme preparations proved to have a more pronounced antioxidant activity. The highest EE (95.28%) was recorded at WPC:MD ratio of 60:40. In vitro enzymatic hydrolysis protocol simulating digestion in the gastrointestinal tract was used to study the effect of capsule structural characteristics on the kinetics of polyphenol release. The percentage of o polyphenols released from capsules ranged from 70% to 83% after two hours of digestion, which confirmed the effectiveness of microencapsulation technology. Conclusion. The research confirmed the possibility of using polyphenols obtained by the biotechnological method from oat bran as functional ingredients. Eventually, they may be used in new functional products with bifidogenic properties. Whey protein can be used to encapsulate polyphenols as the wall material of microcapsules.